Large‐scale high‐resolution pluvial flood hazard mapping using the raster‐based hydrodynamic two‐dimensional model FloodAreaHPC. (18th January 2017) - Tyrna, B.; Assmann, A.; Fritsch, K.; Johann, G.
Abstract : Two‐dimensional (2D) hydraulic models are widely used as tools for flood hazard mapping and also to support flood risk management. Yet, only few models are capable of using high‐resolution terrain data (raster‐based Digital Terrain Model with 1 m spatial resolution) on a large scale (hundreds of square kilometres and more). Central to the model approach presented in this article is the raster‐based 2D model High Performance Computing version of FloodArea (FloodAreaHPC), which allows for multicore processing, thus being able to model large areas without having to make compromises regarding spatial details. The model has been applied for inundation modelling of rivers, dike breaks, and heavy rainfall runoff (pluvial flooding). For the latter case, the model is coupled with a hydrologic preprocessor data base which provides spatially and temporally variable runoff coefficients based on land use, soil, and slope. The case study presented in this study has an area of 144 km 2 and is located close to Dortmund in Western Germany. The modelling results of two heavy rainfall scenarios, presented in analogue and digital flood hazard maps, were used in a Public Relations (PR) campaign to inform the public about pluvial flood risk and possible mitigation measures.